How to develop and execute a public health agenda: From grass roots to legislation. (13th January 2017) - Berger, Stuart
Abstract: Recent experiences with lay public cardiopulmonary resuscitation and use of ambulatory external defibrillators have been demonstrated to improve survival from out-of-hospital cardiac arrests from an abysmal 10% or less to as high as 30%. Though rare, sudden cardiac arrest in presumably healthy young people have been highly publicised over the last 25 years and have motivated the institution of school- and community-based programmes that facilitate first-responder resuscitation, including defibrillation. These efforts often begin at a grass roots level (usually parent-inspired advocacy groups) and through collaborative activities involving the schools, local businesses, and local administrative agencies are now having a meaningful impact in selected communities. The current focus of these activities is on school- and sports venue-based ambulatory external defibrillator programmes and formal cardiopulmonary resuscitation education in high schools. The extension of these programmes to the level of state mandates has been slower, and even when enacted, public funding has usually not been approved.